Legalization of Hemp and the Contribution to Japanese Economy - Wee, Maszeli; Hassan, Asmadi; Abdullah, Alias (WILAYAH: The International Journal of East Asian Studies, 2022)
Recently, the hemp plant has gained worldwide attention due to its great potential. Japan is among the countries that have not fully legalized its usage. Hence it is seen as being left behind to that of the countries that have legalized the plant. Japan is bound by the Taima Torishimari Hou (Cannabis Control Act) which stipulates that hemp should be strictly controlled as it is classified as being part of the cannabis family. Although the demand for hemp products is increasing globally every year, Japan is not able to take advantage. This article examines some aspects of the use of hemp in Japanese society as well as its potential to contribute to the country’s economy. This study employs a qualitative method which is based on primary and secondary sources. The result of the analysis explains the economic opportunities as well as the benefits of legalized hemp usage in Japan. The study found that Japan’s national revenue will increase if hemp is fully legalized and it is no longer bound by the Taima Torishimari Hou.